The social brain meets neuroimaging - Dunbar, R (2012)
Recent neuroimaging studies in humans have indicated that individual differences in social network size correlate with amygdala volume and the volume of brain regions associated with theory of mind. A new article demonstrates that this is also true for monkeys. Taken together, these findings provide crucial support for the social brain hypothesis. © 2011 Elsevier Ltd.